Pelatihan Praktikum IPA SD bagi Guru SD di Kabupaten Tapanuli Tengah - Dongoran, Jhonas; Manik, Cici Andriani; Br. Bangun, Reh Syerina; Aritonang, Aldo Yehezkiel; Simanjuntak, Dairi Sapta Rindu (PUAN INDONESIA, 2024)
One of the problems with education in Indonesia, especially in Central Tapanuli Regency, is the unequal distribution of teachers, especially in certain skills, for example science teachers. On the one hand, there are professional demands on teachers, meaning that teachers are the determining factor in the success of a quality learning process, so that whether or not education achieves its goals is always linked to the work of teachers. Therefore, efforts made to improve the quality of education should start from improving the quality of teachers. One solution related to the problem above is to provide practical science training for elementary school teachers who do not have a science background. The form of this practicum adapts to the types of experiments in elementary school, namely it is simple and can be carried out by students themselves. The evaluation carried out during this PPM activity consists of 2 forms, namely performance evaluation carried out by the PPM team and evaluation in the form of a questionnaire filled in by the teacher participants. From the performance evaluation, participants whose teachers took part in training activities had an average activity score of 84.3, which was in the good category. Meanwhile, from the questionnaire it can be concluded that similar training is very necessary to increase experience and knowledge, especially science practicum